Development of Comprehensible Prescription Label Instructions: A Study Protocol for a Mixed-Methods Approach - Maghroudi, Ekram; van Hooijdonk, Charlotte M. J.; van Dijk, Liset; Boland, Gudule; de Haas, Channah; Journée-Gilissen, Marleen; van der Velden, Janneke; Vervloet, Marcia; Westerhof, Henk; Rademakers, Jany J. D. J. M.; Borgsteede, Sander D. (Frontiers in Pharmacology, 2020)
Introduction Patients receive information about their medication from different sources, including prescription labels. These labels are physically attached to each package dispensed to patients and contain the most important instructions on how to use the medication correctly. However, many patients experience difficulties in understanding and applying the instructions on these labels correctly, especially patients with limited health literacy. The aim of this study is to investigate the comprehensibility of prescription label instructions among patients with adequate and limited health literacy skills, and to implement improvements in primary health care. Methods We used a mixed-methods approach, which consisted of four phases. Phase 1 (desk research) was divided into a systematic literature review on the comprehensibility of prescription label instructions (1a) and a content analysis of the textual elements in Dutch prescription label instructions (1b). In phase 2 (patient studies), semi-structured interviews were conducted to investigate the comprehensibility of seven prescription labels among patients with different health literacy skills (2a), and a quantitative study in which the comprehensibility of six optimized prescription labels was compared among patients with different health literacy skills (2b). Patient studies were conducted in eight Dutch pharmacies. In phase 3 optimized prescription label instructions were implemented in national medication databases which has been supported by a guideline (3a), and education of pharmacy workers (3b). Phase 4 consists of evaluating the optimized prescription label instructions by experiences from patients and pharmacists. Anticipated Results This mixed-methods approach will result in scientific publications of the individual studies, and a guideline on how to compose comprehensible prescription label instructions to be put on medication packages. Optimized prescription label instructions will be implemented in national medication databases. Discussion This protocol describes a mixed-method research to compose and implement comprehensible prescription label instructions and will lead to knowledge about the comprehensibility of textual elements in these labels, with specific attention for patients with limited health literacy. Implementation of optimized prescription label instructions will lead to a better understanding of them, which may contribute to improved medication adherence. A limitation is that non-textual aspects of prescription labels are not investigated.